E-COMMERCE USAGE AND INDONESIAN MSME’S PERFORMANCE - Memarista, Gesti; Gunawan, Erick Teofilus; Kristina, Natalia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to examine the e-commerce usage effect on the performance of MSMEs in Indonesia. The samples used were 157 MSME owners in Indonesia. This study uses the respondent which use e-commerce in their business. The respondent’s data will process by using PLS-SEM. The results of this study indicate that the use of e-commerce can improve the financial performance of MSMEs, internal processes within MSMEs, consumer satisfaction from MSMEs, and business growth and learning within MSMEs. The use of e-commerce has been proven to be able to increase innovation in the MSME operational system, which is able to cut many internal business processes that are less effective and efficient, reduce delay times, increase the market share of MSMEs through online sales, and ultimately increase sales to MSMEs. The use of e-commerce is an important key for MSMEs to be more competitive and survive in the long term. Keyword: business growth and studies; customer satisfaction; e-commerce use; financial performance; internal process;